Posterior cricoarytenoid muscle electrophysiologic changes are predictive of vocal cord paralysis with recurrent laryngeal nerve compressive injury in a canine model. (26th April 2016) - Puram, Sidharth V.; Chow, Harold; Wu, Che‐Wei; Heaton, James T.; Kamani, Dipti; Gorti, Gautham; Chiang, Feng Yu; Dionigi, Gianlorenzo; Barczynski, Marcin; Schneider, Rick; Dralle, Henning; Lorenz, Kerstin; et al.
Abstract : Objectives/Hypothesis: Injury to the recurrent laryngeal nerve (RLN) is a dreaded complication of endocrine surgery. Intraoperative neural monitoring (IONM) has been increasingly utilized to assess the functional status of the RLN. Although the posterior cricoarytenoid muscle (PCA) is innervated by the RLN as the abductor of the larynx, PCA electromyography (EMG) is infrequently recorded during IONM and PCA activity after RLN compressive injury remains poorly characterized. Study Design: Single‐subject prospective animal study. Methods: We employed a canine model to identify postcricoid EMG correlates of postoperative vocal cord paralysis (VCP). Postcricoid electrode recordings were obtained before and after compressive RLN injury associated with VCP. Results: Normative postcricoid recordings revealed mean amplitude of 1288 microvolt (μV) and latency of 8.2 millisecond (ms) with maximum (1 milliamp [mA]) vagal stimulation, and mean amplitude of 1807 μV and latency of 3.5 ms with maximum (1 mA) RLN stimulation. Following injury that was associated with VCP, there was 62.1% decrement in postcricoid EMG amplitude with maximum vagal stimulation and 80% decrement with maximum RLN stimulation. Threshold stimulation of the vagus increased by 23%, and there was a corresponding 42% decrease in amplitude. For RLN stimulation, latency increased by 17.3% following injury, whereas threshold stimulation increased by 61% with 35.5% decrement in EMG amplitude. Thus, if RLN amplitude decreases by ≥ 80%, with absolute amplitude of ≤ 300 μV or less and latency increase of ≥ 10%, RLN injury is likely associated with VCP. Conclusion: Our results predict postoperative VCP based on postcricoid electromyographic IONM and may guide surgical decision making. Level of Evidence: NA Laryngoscope, 126:2744–2751, 2016